ACADEMIC INFORMATION SYSTEM WEB BASED AT MADRASAH ALIYAH AL – SYAHNI RUMBAI JAYA TEMBILAHAN - Nadriati, Sri; Saipul, Saipul; Muharmi, Yulya (LPPM STMIK Dharmapala Riau, 2021)
The development of information technology is very rapid and is needed in all things, especially in the world of education. Madrasah Aliyah Al – Syahni is a high school (SLTA) for the continuation of the junior high school level. The construction of school websites and the construction of web-based academic information systems are some of the uses of information technology. With information technology, it is possible for academic data to be processed quickly and easily so that the presentation of the required academic information report can be obtained accurately, quickly and efficiently. The research methods used in this study were qualitative, observation, interviews and questionnaires. While the development of the system using the programming language PHP (Personal Home Page), HTML (Hyper Text Markup Language), MySQL database. This research program is expected to later be able to help Madrah Aliyah Al - Syahni Rumbai Jaya Tembilahan in processing value data, students, teachers, and with the Madrasa Aliyah Al - Syahni website it is hoped that it will be an attraction for parents to send their children to Madrasah Aliyah Al - Syahni.